Klinický obraz a léčba myopatie a neuropatie u kriticky nemocných pacientů - Latronico, Nicola; Rasulo, Frank A (Current Opinion in Critical Care (České vyd.), 2010)
PURPOSE OF REVIEW: Critical illness myopathy and neuropathy are common complications in the ICU, causing limb and respiratory muscle weakness. We review the most recent data concerning their presentation, diagnosis and treatment. RECENT FINDINGS: Limb muscle strength can be reliably assessed by using the Medical Research Council scale or handgrip dynamometry. A Medical Research Council sum score below 48 or mean Medical Research Council score below 4 (antigravity strength) across all testable muscle groups, and a force value of less than 11 kg-force for men and less than 7 kg-force for women at dominant-hand dynamometry identify ICU-acquired weakness in previously healthy individuals admitted to an ICU for nonneuromuscular disorder. Clinical signs, together with measurements of the maximal inspiratory and expiratory pressures and vital capacity, are important to timely diagnose respiratory muscle weakness. Electrophysiological testing is usefully implemented in unconscious patients or in awake patients who do not improve despite appropriate treatments. Early physiotherapy in the ICU can increase the proportion of patients reaching an independent functional status following their ICU stay. Critical illness myopathy and neuropathy may occur outside the ICU; however, exact estimates are lacking. SUMMARY: Systematic application of diagnostic criteria and early physiotherapy may help clinicians to timely diagnose critical illness myopathy and neuropathy and to reduce the associated morbidity.
Keywords: Electrophysiology; hyperglykemie; polyneuropatie; lidé; elektromyografie; neuropatie kriticky nemocných; Humans; Hyperglycemia; elektrofyziologické jevy; svalová slabost; Polyneuropathies; Electromyography; Critical Care; péče o pacienty v kritickém stavu; elektrofyziologie; fyzioterapie; Muscle Weakness; Electrophysiological Phenomena; stupnice Medical Research Council; myopatie kriticky nemocných; techniky fyzikální terapie; Physical Therapy Modalities